2018
DOI: 10.4103/jovr.jovr_57_18
|View full text |Cite
|
Sign up to set email alerts
|

An update on optical coherence tomography angiography in diabetic retinopathy

Abstract: Optical coherence tomography angiography (OCTA) is a novel non-invasive imaging modality for 3-dimensional visualization of retinal and optic nerve capillary networks. In this article, a comprehensive review of relevant original articles in the PubMed database was performed using the search terms “diabetic retinopathy,” “diabetic macular edema,” “diabetes mellitus,” and “optical coherence tomography angiography.” OCTA was found to detect microvascular changes early in diabetes mellitus, even before they become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 115 publications
(360 reference statements)
2
36
0
Order By: Relevance
“…DR produces a decrease in capillary vascular mesh in superficial and deep plexuses, which is greater as the severity of DR increases,3335 and is earlier and more pronounced in the deep plexus than in the superficial one 5,8,27. Similarly, in our report, the mean VD in both plexuses is reduced in patients with DR versus controls.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…DR produces a decrease in capillary vascular mesh in superficial and deep plexuses, which is greater as the severity of DR increases,3335 and is earlier and more pronounced in the deep plexus than in the superficial one 5,8,27. Similarly, in our report, the mean VD in both plexuses is reduced in patients with DR versus controls.…”
Section: Discussionsupporting
confidence: 81%
“…Likewise, there is a rising number of publications about OCTA and DR,27 however, nowadays the application of this new technology in clinical practice has still not been settled down. Through the application of image processing and analysis software, OCTA allows us to compare data of the main changes in the macula of diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA is a new imaging technique which can assess the retinal and choroidal microvasculature. [2][3][4][5][6][7][8][9][10][11][12] It allows demonstration of the blood flow in both superficial and deep retinal capillary layers, so it can delineate the microvascular changes in DR, such as irregular FAZ, areas of capillary dropout and neovascularization, which have serious effects on visual acuity. 15 The aim of the current study was to demonstrate the impact of these microvascular changes on the vision of patients with DR by analyzing the correlation between visual acuity and retinal vessel density, as well as the area of FAZ, using OCTA.…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7][8] The retinal microvascular changes in DR may lead to visually fatal complications, including macular ischemia, neovascularization and macular edema. 9 Recent research has highlighted the potential role of this new imaging modality in assessing the retinal microvascular abnormalities in various retinal diseases, including DR. [7][8][9][10] The quantitative OCTA parameters, such as foveal avascular zone (FAZ) area, vessel density, and perfusion density in the superficial and deep capillary plexus, may have a useful role in the early detection of subclinical disease and may also provide valuable biomarkers in monitoring the progression of DR and preventing its severe complications. [11][12][13] The aim of the current study was to assess the correlation between best corrected visual acuity (BCVA) and different OCTA parameters in patients with DR.…”
Section: Introductionmentioning
confidence: 99%
“…The prominent difference in vessel alteration and the FAZ indicated that the retinal vasculature may change in some patients with DME after DEX implantation. Although diabetic retinopathy would uneventfully enlarge the FAZ, which progressed with the disease severity,18 no severe complications, such as vitreous hemorrhage or tractional retinal detachment, were found during the two-month period. In addition, the blood sugar level was 212 mg/dL and 171 mg/dL before and two months after the DEX implantation, and the glycosylated hemoglobin was 7.3 percent and 7.0 percent before and two months after the DEX implantation, implied that the progression of diabetes mellitus was not likely.…”
Section: Discussionmentioning
confidence: 91%